2021
DOI: 10.1007/s11418-021-01505-1
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses LGR5(+) colorectal cancer stem cells by inducing autophagy and via repressing TFAP2A-mediated ECM pathway

Abstract: Colorectal cancer stem cells (CSCs) have the potential for self-renewal, proliferation, and differentiation. And LGR5 is a stem cell marker gene of colorectal cancer. Curcumin can suppress oncogenicity of many cancer cells, yet the effect and mechanism of curcumin in LGR5(+) colorectal cancer stem cells (CSCs) have not been studied. In this study, we studied the effect of curcumin on LGR5(+) colorectal CSCs using the experiments of tumorsphere formation, cell viability and cell apoptosis. Then autophagy analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Very recently, research based on this model shows the effectiveness of curcumin in various forms of cancer [67].…”
Section: Curcumin and Latest Cancer Applicationsmentioning
confidence: 99%
“…Very recently, research based on this model shows the effectiveness of curcumin in various forms of cancer [67].…”
Section: Curcumin and Latest Cancer Applicationsmentioning
confidence: 99%
“…These studies suggest that curcumin inhibits proliferation, induces cell cycle arrest and apoptosis through different mechanisms, in different types of tumor cell lines. There is evidence that curcumin reduces the expression of many different enzymes, transcription factors, inflammatory cytokines, growth factors, and other cell signaling components that are important for tumor growth and progression ( Table 2 ) ( Lee et al, 2011 ; Wang et al, 2019a ; Zhang et al, 2020 ; Ebrahimi et al, 2021 ; Liang et al, 2021 ; Mao et al, 2021 ; Shi et al, 2021 ; Sun and Fang, 2021 ). For instance, in many studies of various tumor cell lines, curcumin has been found to downregulate the expression of the transcription factor NF-κB, which is normally highly expressed in tumor cells and is known to promote development, metastasis and tumor growth.…”
Section: The Effectiveness Of Polyphenolsmentioning
confidence: 99%
“…Curcumin also induces tumor cell apoptosis through caspase-dependent pathways and reduces the expression of anti-apoptotic proteins. Moreover, to in vitro studies, the properties of curcumin have also been studied in in vivo ; overall demonstrating that curcumin has anti-proliferative effects ( Lee et al, 2011 ; Wang et al, 2019a ; Zhang et al, 2020 ; Ebrahimi et al, 2021 ; Liang et al, 2021 ; Mao et al, 2021 ; Shi et al, 2021 ; Sun and Fang, 2021 ). For instance, a mouse model of colorectal cancer treated with an intraperitoneal injection of curcumin demonstrated that curcumin inhibits tumor growth with favorable prognosis for overall survival.…”
Section: The Effectiveness Of Polyphenolsmentioning
confidence: 99%
“…Curcumin, alone or in combination with piperine, inhibited the formation of tumorspheres in breast cancer cells, interfering with the stem-cell signaling pathways involved in carcinogenesis [ 76 ]. Moreover, curcumin could prevent the cell proliferation of LGR5 + colorectal cells by triggering autophagy and blocking via the TFAP2-mediated ECM pathway [ 77 ]. In recent years, several studies have shown that natural polyphenols may be used as adjuvant therapy in association with traditional treatment to reduce CSC drug resistance [ 69 , 70 ].…”
Section: Natural Products As Adjuvant Against Cancer Stem Cellsmentioning
confidence: 99%